2023
DOI: 10.3390/v15020309
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of SARS-CoV-2: The Dominant Role of Arginine in Mutations and Infectivity

Abstract: Background, Aims, Methods, Results, Conclusions: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a global challenge due to its ability to mutate into variants that spread more rapidly than the wild-type virus. The molecular biology of this virus has been extensively studied and computational methods applied are an example paradigm for novel antiviral drug therapies. The rapid evolution of SARS-CoV-2 in the human population is driven, in part, by mutations in the receptor-binding domain (RBD) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 83 publications
(178 reference statements)
0
7
0
Order By: Relevance
“…Pioneering research on RAAS has resulted in the discovery of the first orally active ARB antagonist, Losartan (DUP753), followed by the development of a series of other potent Sartans for the treatment of hypertension [ 88 ]. Since ACE2, which is a part of RAAS and the entry point of SARs-CoV-2 in the cell, Sartans bearing anionic groups, tetrazolate, and carboxylate, were investigated as possible antivirals for the treatment of COVID-19, either by blocking entry or replication of the virus [ 13 , 22 , 23 ]. Extensive clinical studies have shown that ARBs are beneficial in the treatment of hypertensive patients infected by COVID-19 [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pioneering research on RAAS has resulted in the discovery of the first orally active ARB antagonist, Losartan (DUP753), followed by the development of a series of other potent Sartans for the treatment of hypertension [ 88 ]. Since ACE2, which is a part of RAAS and the entry point of SARs-CoV-2 in the cell, Sartans bearing anionic groups, tetrazolate, and carboxylate, were investigated as possible antivirals for the treatment of COVID-19, either by blocking entry or replication of the virus [ 13 , 22 , 23 ]. Extensive clinical studies have shown that ARBs are beneficial in the treatment of hypertensive patients infected by COVID-19 [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“… Chemical structures of BisA (4-Butyl-N,N0-bis{[[20-(2H-tetrazol-5-yl)]biphenyl-4-yl] methylimidazolium bromide), BisB (4-Butyl-2-hydroxymethyl-N,N0-bis{[20-(2H-tetrazol-5-yl)-biphenyl-4-yl]- methyimidazolium bromide), BisC (2-Butyl-4-chloro-5-hydroxymethyl-N,N0-bis{[20-(2Htetrazol-5-yl)biphenyl-4-yl]methylpimidazolium bromide) (Dialkylated losartan), BisD (2-Butyl-N,N0-bis{[20-(2H-tetrazol-5-yl)biphenyl-4-yl]methyl}x In imidazolium bromide). Note that the tetrazole group is deprotonated at physiological pH [ 13 , 22 , 23 ]. Illustrations were made with MarvinSketch, version 22.22.0 [ 24 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Our research team discovered and synthesized a new cohort of antihypertensive drugs that were predicted to stably dock at catalytic site and semi-stably at furin-cleavage site (residues 681-686) of the transmembrane angiotensin-converting enzyme 2 (ACE2), which is the primary receptor for attachment and entry of SARS-CoV-2 into susceptible host tissues [19][20][21][22][23][24]. We refer to this new class of drugs as "bisartans" since they share structural similarities to the "sartan" therapeutics (e.g., Losartan, Olmesartan, Telmisartan, Irbersartan, Valsartan, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, “arginine blockers” (ARBs; e.g., Sartans) containing anionic tetrazole and/or carboxyl functional groups, and in particular Bisartans containing two tetrazole moieties with increased acidity, represent promising repurposed antiviral drugs [23] . Thus, drugs in the Sartan family can block furin activity (and subsequent infection) by obstructing basic amino acids of cleavage sites [24] , [25] , [26] . Clinical studies have shown the beneficial effect of ARBs Telmisartan, Candesartan, Losartan in hypertension patients infected by SARs-CoV-2 compared to patients not taking ARBs [27] , [28] .…”
Section: Introductionmentioning
confidence: 99%